Special Thai Oolong Tea: Chemical Profile and In Vitro Antidiabetic Activities - Rujanapun, Narawadee; Jaidee, Wuttichai; Duangyod, Thidarat; Phuneerub, Pravaree; Paojumroom, Napassawan; Maneerat, Tharakorn; Pringpuangkeo, Chuchawal; Ramli, Salfarina; Charoensup, Rawiwan (Frontiers in Pharmacology, 2022)
Special Thai Oolong tea is the Oolong tea (Camellia sinensis (L.) Kuntze) steamed with selected Thai botanical drugs. Oolong tea steamed with ginger (Zingiber officinale), lemongrass (Cymbopogon citratus) and celery (Anathallis graveolens L.) is called Eternity tea (EN), whereas Peaceful Rest (PR) tea is made of Oolong tea leaves steamed with Indian gooseberry (Phyllanthus emblica), Turkey berry (Solanum torvum) and wild betel leaf bush leaves (Piper sarmentosum). Oolong tea is known for numerous biological activities including antidiabetic properties, however the effect of the additional botanical drugs on the biological activities of special Oolong teas has not yet been explored. From the results, PR extract exhibited the best activity in the in vitro assays relevant to antidiabetic properties such as chemical antioxidant, anti-inflammation, anti-adipogenesis, enzyme inhibition and glucose uptake and consumption. The UHPLC-QTOF-MS/MS profiles of PR and EN extracts indicated different chemical profiles than Oolong tea. For instance, gingerdiol and gingerol were detected in EN, whereas Piperettine I was detected in PR. Therefore, it was inferred that among the three tea extracts, the additional compounds in PR contributed to good activities compared to Oolong and EN. It is also important to highlight, PR extract inhibited the glucose uptake and consumption by adipocytes and skeletal muscle at concentration of 500 and 100 μg/mL respectively, as good as metformin activity (P<0.05). Findings from this study support the antidiabetic potential of PR tea.